Nurse's vision on co-responsibility in cases of premature babies in the neonatal intensive care unit (Research, Society and Development, 2022)
Objective: to know the nurse's view of co-responsibility in cases of premature babies in the Neonatal Intensive Care Unit (NICU). Method: This is a qualitative study with descriptive and exploratory approach, in the municipality of Juazeiro do Norte - CE, having as a place of study the reference maternity of the Cariri macroregion. Data collection was performed through a questionnaire whose answers were given by nurses working in the NICU were submitted to analysis. For data analysis it was used the content analysis model proposed by Bardin (2011), in which the material went through a three-step analysis: pre-analysis, exploration of the material and treatment of results thus emerging four categories. Results: The sample in the research period was 08 (eight) nurses, however due to difficulties in time management and intense work routine it was not possible for 02 (two) nurses to participate in the research. After prior reading of the questionnaire and the answers, it was possible to establish four categories, they are: defining humanized care (category 1); co-responsibility and its materialization in humanized care (category 2); materializing co-responsibility and its possible difficulties (category 3); characterizing care in the Neonatal ICU (category 4). Conclusion: It was found the relevance of the multiprofessional team together with the family, since the harmony of the two subjects provided that the care to the individual is performed in the fullness of its totality. Conclusion: The relevance of the multidisciplinary team was verified together with the family, since the harmony of the two subjects provided that care to the individual is performed in the fullness of its tone.